In vivo Population Averaged Stereotaxic T2w MRI Brain Template for the Adult Yucatan Micropig - Chang, Stephano J.; Santamaria, Andrea J.; Sanchez, Francisco J.; Villamil, Luz M.; Pinheiro Saraiva, Pedro; Rodriguez, Jose; Nunez-Gomez, Yohjans; Opris, Ioan; Solano, Juan P.; Guest, James D.; Noga, Brian R. (Frontiers in Neuroanatomy, 2020)
Population averaged brain templates are an essential tool for imaging-based neuroscience research, providing investigators with information about the expected size and morphology of brain structures and the spatial relationships between them, within a demographic cross-section. This allows for a standardized comparison of neuroimaging data between subjects and provides neuroimaging software with a probabilistic framework upon which further processing and analysis can be based. Many different templates have been created to represent specific study populations and made publicly available for human and animal research. An increasingly studied animal model in the neurosciences that still lacks appropriate brain templates is the adult Yucatan micropig. In particular, T2-weighted templates are absent in this species as a whole. To address this need and provide a tool for neuroscientists wishing to pursue neuroimaging research in the adult micropig, we present the construction of population averaged (n=16) T2-weighted MRI brain template for the adult Yucatan micropig. Additionally, we present initial analysis of T1-weighted (n=3), and diffusion-weighted (n=3) images through multimodal registration of these contrasts to our T2 template. The strategies used here may also be generalized to create similar templates for other study populations or species in need of template construction.